Biphasic plating improves the mechanical performance of locked plating for distal femur fractures. (22nd January 2021) - Epari, Devakara R.; Gurung, Roshan; Hofmann-Fliri, Ladina; Schwyn, Ronald; Schuetz, Michael; Windolf, Markus
Abstract: Internal fixation by plate osteosynthesis is the gold standard treatment for distal femur fractures. Despite improvements that preserve the biological conditions for bone healing, there are concerns standard locked plating constructs may be overly stiff. Biphasic plating is a novel concept designed to provide suitable fracture motion and increased implant strength to support early full weight-bearing. This study aims to demonstrate that the Biphasic Plate can be incorporated into a pre-contoured distal femur plate while providing adequate flexibility and increased implant strength. The mechanical performance of the Biphasic Plate (BP) was investigated in comparison to a standard locking plate for the distal femur (LCP-DF). Constructs were formed by mounting the implants on a bone substitute. The construct stiffness and strength under axial loading and the magnitude of interfragmentary movement were determined using finite element analysis. The Biphasic Plate exhibited a bi-linear stiffness response; at low loads, the BP construct was 55% more compliant and at high loads 476% stiffer than the LCP-DF. The Biphasic Plate provided more consistent interfragmentary movement over a wider loading range. At partial weight-bearing loads, the Biphasic Plate produced larger interfragmentary movements (0.18 vs. 0.04 mm). However, at loads equivalent to full weight-bearing, the maximum movements were substantially smaller than the LCP-DF construct (1.5 vs. 3.5 mm). The increased flexibility at low loads was provided without sacrificing implant strength with peak stress in the Biphasic Plate 63% lower than the LCP-DF construct. The biphasic plating concept can be successfully incorporated into anatomically contoured distal femur plates while providing adequate flexibility and increasing implant strength.